Seismic projection of non-rectangular reinforce concrete walls - Goenadibrata, Yohan Resa. (2013)
Conveniently, RC walls have been ever present in the core of the buildings. Non-rectangular-shaped walls like L-shaped and T-shaped have been studied so to cater the needs of the engineers. These walls are designed with high shear-span ratio and well-detailed boundary elements.